Current evidence of extracorporeal shock wave therapy in chronic Achilles tendinopathy. (December 2015) - Gerdesmeyer, Ludger; Mittermayr, Rainer; Fuerst, Martin; Al Muderis, Munjed; Thiele, Richard; Saxena, Amol; Gollwitzer, Hans
Abstract: Chronic Achilles tendinopathy has been described as the most common overuse injury in sports medicine. Several treatment modalities such as activity modification, heel lifts, arch supports, stretching exercises, nonsteroidal anti-inflammatories, and eccentric loading are known as standard treatment mostly without proven evidence. After failed conservative therapy, invasive treatment may be considered. Extracorporeal shock wave therapy (ESWT) has been successfully used in soft-tissue pathologies like lateral epicondylitis, plantar fasciitis, tendinopathy of the shoulder and also in bone and skin disorders. Conclusive evidence recommending ESWT as a treatment for Achilles tendinopathy is still lacking. In plantar fasciitis as well as in calcific shoulder tendinopathy shock wave therapy is recently the best evaluated treatment option. This article analysis the evidence based literature of ESWT in chronic Achilles tendinopathy. Recently published data have shown the efficacy of focused and radial extracorporeal shock wave therapy. Highlights: This review shows efficacy of extracorporeal shock wave therapy. Focused and radial shock waves both show efficacy in chronic Achilles tendinopathy. All treatments should be done without local anesthesia.